2020
DOI: 10.1371/journal.pone.0243868
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescription practices among prescribers for children under five at public health centers III and IV in Mbarara district

Abstract: Introduction Rational use of medicines requires that patients receive medications appropriate to their clinical needs. Irrational prescription of antibiotics has been reported in many health systems across the world. In Uganda, mainly nurses and assistant medical officers (Clinical officers) prescribe for children at level III and IV primary care facilities (health center II and IV). Nurses are not primarily trained prescribers; their antibiotic prescription maybe associated with errors. There is a need to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Description of antibiotic use errorsThis research observed 36.5% of medical prescriptions containing errors, with a total of 34.5% of antibiotics being improper prescribed.Iftikhar et al, and Denny et al, observed convergent rates of 40.8% and 22.9% improper prescriptions, respectively (47,48). A survey by Santander et al found a convergent rate of 51.9 % of improper medical prescriptions, Okello et al, (68.4%)(49,50). In this research, 57.1%, 27.7%, 11.6% and 3.6% of the prescriptions presented a, two, three and four errors respectively.…”
supporting
confidence: 46%
“…Description of antibiotic use errorsThis research observed 36.5% of medical prescriptions containing errors, with a total of 34.5% of antibiotics being improper prescribed.Iftikhar et al, and Denny et al, observed convergent rates of 40.8% and 22.9% improper prescriptions, respectively (47,48). A survey by Santander et al found a convergent rate of 51.9 % of improper medical prescriptions, Okello et al, (68.4%)(49,50). In this research, 57.1%, 27.7%, 11.6% and 3.6% of the prescriptions presented a, two, three and four errors respectively.…”
supporting
confidence: 46%
“…Iftikhar et al [ 15 ], and Denny et al [ 31 ], observed convergent rates of 40.8% and 22.9% improper prescriptions, respectively. A survey by Santander et al found a similar rate of 51.9% of improper medical prescriptions [ 32 ], while Okello et al found a rate of 68.4% [ 33 ]. In the present research, 57.1%, 24.1%, 10.7%, and 8.0% of the prescriptions presented one, two, four, and three errors, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are comparable with those of studies conducted in Mbarara and Bushenyi districts. 23 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…20,21 Nurses made half the evaluated prescriptions, a similar finding to other studies conducted in Ghana and Uganda. [21][22][23] This can be attributed to the fact that primary care facilities in Uganda serve majority of the population and are mainly managed by nurses with a few clinical officers at HC IIIs and HC IVs, plus one or two medical officers at HC IVs. 15 Reforms authorising nurses to prescribe medicines have gained momentum in the recent past globally.…”
Section: Discussionmentioning
confidence: 99%